Testing the Utility of Alternative Metrics of Branch Support to Address the Ancient Evolutionary Radiation of Tunas, Stromateoids, and Allies (Teleostei: Pelagiaria). (6th May 2021) - Arcila, Dahiana; Hughes, Lily C; Meléndez-Vazquez, Bruce; Baldwin, Carole C; White, William T; Carpenter, Kent E; Williams, Jeffrey T; Santos, Mudjekeewis D; Pogonoski, John J; Miya, Masaki; Ortí, Guillermo; Betancur-R, Ricardo
Abstract: The use of high-throughput sequencing technologies to produce genome-scale data sets was expected to settle some long-standing controversies across the Tree of Life, particularly in areas where short branches occur at deep timescales. Instead, these data sets have often yielded many well-supported but conflicting topologies, and highly variable gene-tree distributions. A variety of branch-support metrics beyond the nonparametric bootstrap are now available to assess how robust a phylogenetic hypothesis may be, as well as new methods to quantify gene-tree discordance. We applied multiple branch-support metrics to a study of an ancient group of marine fishes (Teleostei: Pelagiaria) whose interfamilial relationships have proven difficult to resolve due to a rapid accumulation of lineages very early in its history. We analyzed hundreds of loci including published ultraconserved elements and newly generated exonic data along with their flanking regions to represent all 16 extant families for more than 150 out of 284 valid species in the group. Branch support was typically lower at inter- than intra-familial relationships regardless of the type of marker used. Several nodes that were highly supported with bootstrap had a very low site and gene-tree concordance, revealing underlying conflict. Despite this conflict, we were able to identify four consistent interfamilial clades, each comprised of two or three families. Combining exons with their flanking regions also produced increased branch lengths at the deep branches of the pelagiarian tree. Our results demonstrate the limitations of employing current metrics of branch support and species-tree estimation when assessing the confidence of ancient evolutionary radiations and emphasize the necessity to embrace alternative measurements to explore phylogenetic uncertainty and discordance in phylogenomic data sets.[Concatenation; exons; introns; phylogenomics; species-tree methods; target capture.]